Existence and almost everywhere regularity of isoperimetric clusters for fractional perimeters. (April 2017) - Colombo, M.; Maggi, F.
Abstract: The existence of minimizers in the fractional isoperimetric problem with multiple volume constraints is proved, together with a partial regularity result.